Talent balancing : staffing your company for long-term success - Stedt, Jim, 1948- (Praeger Publishers, 2006)
When the economy was booming, it was hard to find good people. winning the talent war was a popular phrase, and those individuals with the right stuff could command hefty salaries and perks. When the economy crumbled, the headhunters were sent packing. Today, companies are starting to hire again, but instead of recruiting a group of fifty, they're hiring five. They're outsourcing and hiring temps. They're replacing staff due to turnovers, retirements, and areas that were downsized, rather than expanding. They're relying on reduced HR departments and in-house managers and staff to make critical.